Search for pulsed VHE gamma-ray emission from young pulsars with HESS - van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2007)
Aims. We present the results of a search for pulsed very-high-energy (VHE) γ-ray emission from young pulsars using data taken with the HESS imaging atmospheric Cherenkov telescope system. Methods. Data on eleven pulsars, selected according to their spin-down luminosity relative to distance, are searched for y-ray signals with periodicity at the respective pulsar spin period. Special analysis efforts were made to improve the sensitivity in the 100 GeV γ-ray energy domain in an attempt to reduce the gap between satellite and ground-based γ-ray instruments. Results. No significant evidence for pulsed emission is found in any data set. Differential upper limits on pulsed energy flux are determined for all selected pulsars in the approximate γ-ray energy range between 100 GeV and 50 TeV, using different limit determination methods, testing a wide range of possible pulsar light curves and energy spectra. Conclusions. The limits derived here imply that the magnetospheric VHE γ-ray production efficiency in young pulsars is less than 10 of the pulsar spin-down luminosity, requiring spectral turnovers for the high-energy emission of four established γ-ray pulsars, and constrain the inverse Compton radiation component predicted by several outer gap models. © ESO 2007.
Keywords: Gamma rays: observations; Pulsars: individual: Crab pulsar; Pulsars: individual: PSR B1259-63; Pulsars: individual: PSR B1509-58; Pulsars: individual: PSR B1706-44; Pulsars: individual: Vela pulsar